Improving hand hygiene compliance among healthcare workers in intensive care unit: an interventional study - Abdo, Naglaa M.; Al-Fadhli, Mariam (International Journal Of Community Medicine And Public Health, 2018)
Background: Hand hygiene (HH) is one of the most important measures to prevent healthcare-associated infections. The objective of the study was to assess the effectiveness of the augmented multi-interventional approaches on HH compliance rate among intensive care unit (ICU) healthcare workers (HCWs) of Farwaniya Hospital, Kuwait. Methods: An interventional study was conducted in four phases throughout eight months among adult ICU HCWs. First; HCWs, HH compliance rates and alcohol-based hand rub consumption rate (ABHR) were assessed secondly; an augmented multi-interventional approach was implemented, which included administrative support, observation and reporting, education & training, recruiting champions, and maintenance of HH supplies & reminders. Then a washout phase. Finally, re-assessment of HH compliance rates and ABHR. Results: Following the interventions, the overall HCWs’ HH compliance rate increased significantly from 58.81% to 73.17% (p=0.000), for doctors (39.82% vs. 64.93%) and nurses (68.24% vs. 80.18%), p>0.001. Significant improvement of HH compliance rates for most of HH moments, after moments were higher than before moments, p=0.000. ABHR increased significantly from 77.45 ml to 133.33 ml per patient day (95% CI=54.37-57.39, p<0.0001). Conclusions: The applied augmented multi-interventional approach was effective in improving HH compliance rates among ICU HCWs. Sustainability is warranted by continues implementation of this approach.